Specialized Nurse-led Care of Chronic Wounds During Hospitalization and After Discharge: A Randomized Controlled Trial. (January 2023) - Sili, Alessandro; Zaghini, Francesco; Monaco, Dario; Dal Molin, Alberto; Mosca, Nella; Piredda, Michela; Fiorini, Jacopo
ABSTRACT: OBJECTIVE: To evaluate the effectiveness of specialized nurse-led care of patients with chronic wounds, provided both during hospitalization and postdischarge, on wound healing and readmission rates. METHODS: An unblinded randomized controlled trial was conducted. Participants were patients with chronic wounds, randomly assigned to either the experimental group (cared for by wound care nurses both during hospitalization and postdischarge) or to the control group (cared for according to standard practice). Wound healing was identified as the primary outcome. RESULTS: Overall, 1, 570 patients were randomized, 1, 298 of whom were included in the per-protocol analysis (707 in the experimental group and 591 in the control group). Nurse-led wound care quadrupled the probability of healing and reduced the number of treatment weeks and hospital readmissions. CONCLUSIONS: Chronic wound care that was entrusted to specialized nurses improved outcomes in terms of wound healing, repair and regeneration, length of treatment, and rate of readmission, compared with standard practice. Future studies should evaluate the impact of care provided by specialized wound care nurses on patients' quality of life and healthcare costs. Nurse managers should promote the implementation of chronic wound clinical-care pathways entrusted to specialized nurses to improve patients' clinical outcomes and reduce hospital readmissions.